(3CNHGQ ecI heG LGA ajgG ef GdBKGQs - (3CHh GdhdjO eMeO Hf YHO Gddg Hf CMeO GdCRQbj,J (B250 (3g` s
(3ChdgG (B:s
(3PcQ eG cGfJ GdcYHI Ydjg ahb GdeGA bHd Cf jNdb Gddg JYGdi GdSehGJ hGdCQV , heG LGA ai Pdc (B: (3MOKfG GdTjN ebOe GdbQGA bGd CHh GdhdjO eMeO Hf YHO Gddg bGd di LOi CMeO Hf eMeO bGd cYH GdCMHGQ(B: (3cGfJ GdcYHI s
(3BNQgG (B:s
(3JSGb dHWf ecI OjeI JQhi HgG hYdi GdeOjfI JSHd ced cJGH ecI HLejY CNHGQg hCTYGQg , hGdMeO ddg s
(3fSNI fajSIs
(3cJHJ Hbde ajg VHWs
(3HChdgG bQGAg gPG GdcJGH dCHj GdhdjO GdHGLi HNWg Ydi TjNI CHj GdMLGL jhSa Hf aJhMs
(3hELGRI ef GdTjN ddHGLi HLejY eUfaGJg heQhjGJg hHLejY eG jLhR dg QhGjJg ef efbhd heSehY HTQWgs
(3HBNQgG ebGHdJgG GdChdi ebGHdI Ydi CUd eUfag hbs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs